Hadis Rasulullah SAW yang Berkaitan dengan Janabah dan Tayamum - Sukatin, Sukatin; Adhiyah, Adhiyah; Asshidiqi, Hasbi; Masobirin, Masobirin; Nurmania, Nurmania (Multiverse: Open Multidisciplinary Journal, 2023)
Islam stands out as the only religion that places a profound emphasis on cleanliness, purity, and health for humanity, particularly among Muslims, through practices like bathing and tayammum ablution. These practices are divinely commanded to ensure that individuals remain healthy, clean, and free from various impurities. The Islamic faith is not only profound but also adorned with blessings and conveniences bestowed by Allah. As an omniscient deity, Allah facilitates ease in worship to prevent His creations from negligence and disobedience. This facilitation, known as kerhoksoan, becomes evident when accessibility to water poses a challenge. In such instances, Allah has provided a practical solution through the ritual of tayammum. Expanding on the significance of tayammum, it serves as a testament to Allah's benevolence, offering flexibility in adherence to religious practices. This divine accommodation ensures that even under challenging circumstances, believers can maintain spiritual and physical well-being.